Implementasi Media Audiovisual dalam Meningkatkan Kemampuan Menulis Surat Resmi pada Siswa Kelas V SD Muhammadiyah Kota Sorong - Aswad Muhdar; Jondeway Andi Hasan; Moh Saleh Refra; Ana Lestari; Niny Jeni Maipau Maipau (CV. Ulil Albab Corp, 2024)
The activity aimed to describe the effectiveness level of audiovisual media in improving the ability of learning to write official letter at V grade elementary school student in Muhammadiyah Sorong City. This activity was experimental research posttest only control group design type. The total population in this research was 151 people using total sampling. Sample in this activity was clustered on two cluster, VA grade SDN Muhammadiyah 1 Sorong City students as many as 32 students as experimental class (X) and VB grade SDN Muhammadiyah 2 Sorong city students as many as 28 students as control class (Y). Technique of collecting data was done by giving test to each cluster, experimental class and control class. The obtained data were analyzed using statistic descriptive technique and analysis experimental technique t-test third design type. This result of this activity showed that calculation of coefficient comparison of average score students ability in learning to write official letter between experimental class (X) and control class (Y) was obtained as much as 1,82 higher that t-table in significant level of 95% that was t.s. 0,95 = 1,70, then alternative hypothesis (H1) accepted. Thus, using audiovisual media was effectively applied in learning to write official letter at V grade elementary school student in Muhammadiyah sorong city. Based on this result, the researcher suggested using audiovisual media in learning to write official letter at V grade elementary school student in Muhammadiyah Sorong city. Because audiovisual media developing student’s creativity and imagination, especially in using idea, developing and organizing systematically complete and solid essay. This was applied with the aim of the students can improve their ability to write official letter.